Mapeamento de processos e complexidade de um Departamento de Patrimônio de uma IFES - Santos, Rodrigo Eduardo dos (2017)
Public organizations management has undergone major changes in order to modernize. One way to achieve this goal is to modernize People Management. One approach is People Management by Competencies (PMC). PMC incorporates several concepts such as competency, complexity and occupational space. In Brazil, the Decree no. 5707/06 provided the establishment of policies and guidelines for the development of personnel in the federal public administration, autarchic and foundational, among them the Federal Institutions of Higher Education (FIES) and it allowed the PMC to be put in practice. Minor struggles were encountered when the FIES implemented the PMC, such as: the existence of legal premises that do not include PMC in public admission assessments, career plans, and remuneration progress that are not adequate to this new reality, and especially the non-appropriation of the concepts of complexity and occupational space by the current initiatives. Hiring Administrative Technicians in Education (ATE) through a trial of tests and titles, and the difficulty to map their competencies makes it difficult to maneuver the ATE. Being unsatisfied with their activities, the are more prone to deliver unsatisfactorily, as evaluated by their "clients". The goal of this research was to investigate the concept of complexity applied to work processes in the public context with the purpose of allocating servers in positions compatible with their professional performance. The research method used was action research, and the case was the Federal University of São Carlos (FUSCar). The results obtained comprised a proposal for the lack of a model for the internal movement of personnel, which included the mapping of the work processes and the classification of the server’s performance in these processes in levels of complexity. The theoretical discussion and the results achieved brings us to the conclusion that the use of the concepts of complexity and occupational space empower the employees and managers in their decisions about shifts in the organizational structure, by making them aware of their role and their contribution in the different units of the organization.